AB1305 Clinical utility of tuberculosis interferon gamma test (IGT) in patients due to start anti tnf treatment. (23rd January 2014) - Chander, S.; Hajela, V.
Abstract : Background: Anti TNF therapy is a standard treatment in management of patients with Inflammatory Arthritis. This has led to increased risk of infections in this patient subset and one of the major concerns is the increased risk of reactivation of latent Tuberculosis (LTB).British Thoracic Society (BTS) 2005 recommendations suggested patients with previous history of TB or an abnormal CXR should be investigated to rule out Active disease. Patients with Normal CXR who are not on immunosuppressive therapy, a Mantoux should be done for risk stratification. Patients with a Mantoux≥15mm in who have had BCG and≥5mm in patients without BCG should undergo risk stratification using risk stratification tables. Patients who are on immunosuppression should have risk stratification as mantoux wont be helpful (1). Recent NICE guidance advises to consider IGT (Interferon gamma test) or IGT/Mantoux in patients who are immunocompromised, but do not specifically mention about use of these in patients who are on Anti TNF therapy(2). Objectives: We describe our experience of use of IGT as a pre screening tool for latent TB in patients who are being assessed for antiTNF therapy for inflammatory arthritis in a teaching hospital in a low prevalence area (13/100000) Methods: We identified patients who had undergone IGT as a pre screening tool for anti TNF therapy from 18/5/2011 to 01/12/2011. The samples were analysed by using T Spot-TB® Oxford Immunotec, Abingdon, UK assay. The cost of each assay was £69.41. Results: All 104 patients assessed for anti TNF therapy had IGT. 94 patients with inflammatory arthritis were on immunosuppressive therapy (DMARD/Steroids). The total cost of Tspot testing was £7218. There were 3 (3%) indeterminate results. Five (5%) samples could not be processed due to insufficient cells. Five (5%) patients had a positive IGT and 91 patients (87%) had a negative test.Amongst the positives, 2 patients had an abnormal X-ray with a previous history of TB. One of these patients was being treated for active TB and the other was commenced on treatment for latent TB. One patient with a normal CXR and prev h/o TB and 2 other patients with a normal chest x-ray and no h/o TB were deemed low risk and commenced on Anti TNF therapy, after discussion with the chest team. Conclusions: In our low incidence population, we found only 1 patient with latent TB who needed treatment with INH/Rifampicin. The NICE guidance states that all imunocompromised patients should have IGT testing. However it does not mention about its usage in patients who are being assessed for anti TNF therapy. As most of our patients are immunosuppressed secondary to medications or the chronic disease, we would need to identify those who are at increased risk of developing TB. We need to have a robust mechanism in the form of a detailed questionairre, history and clnical examination along with a chest x ray to ensure patients are effectively screened offer IGT to patients who are an increased risk to r/o TB. IGT can be used more effectively by further risk stratification, which would lead to judicious use of resources. References: BTS recommendations for assessing risk and for managing Mycobacterium tuberculosis infection and disease in patients due to start anti-TNF-a treatment. Thorax 2005;60:800–805. NICE clinical guideline 117. Tuberculosis: clinical diagnosis and management of tuberculosis, and measures for its prevention and control. March 2011. Disclosure of Interest: None Declared